A companion to Schopenhauer - Vandenabeele, Bart. (Hoboken : John Wiley & Sons, 2011)
A Companion to Schopenhauer provides a comprehensive guide to all the important facets of Schopenhauer & rsquo;s philosophy. The volume contains 26 newly commissioned essays by prominent Schopenhauer scholars working in the field today. A thoroughly comprehensive guide to the life, work, and thought of Arthur Schopenhauer - Demonstrates the range of Schopenhauer's work and illuminates the debates it has generated - 26 newly commissioned essays by some of the most prominent Schopenhauer scholars working today reflect the very latest trends in Schopenhauer scholarship - Covers the full range of historical and philosophical perspectives on Schopenhauer's work - Discusses his seminal contributions to our understanding of knowledge, perception, morality, science, logic and mathematics, Platonic Ideas, the unconscious, aesthetic experience, art, colours, sexuality, will, compassion, pessimism, tragedy, pleasure, and happiness.
A Companion to Schopenhauer; Contents; Notes on Contributors; Acknowledgments; A Note on Cross-References; Introduction: Arthur Schopenhauer: The Man and His Work; Part I: Nature, Knowledge and Perception; 1: Schopenhauer on Scientific Knowledge; 2: Perception and Understanding: Schopenhauer, Reid and Kant; 3: Schopenhauer's Philosophy of Logic and Mathematics; 4: Schopenhauer's Color Theory; 5: Schopenhauer and Transcendental Idealism; Part II: World, Will and Life; 6: Schopenhauer's Philosophy of the Dark Origin; 7: The Consistency of Schopenhauer's Metaphysics; 8: Schopenhauer on Sex, Love and Emotions9: Schopenhauer and Platonic Ideas; 10: Schopenhauer's On the Will in Nature: The Reciprocal Containment of Idealism and Realism; Part III: Art, Beauty and the Sublime; 11: Schopenhauer's Philosophy of Music; 12: Schopenhauer's Theory of Architecture; 13: The Artist as Subject of Pure Cognition; 14: Schopenhauer on Tragedy and the Sublime; 15: Schopenhauer and the Objectivity of Art; Part IV: Compassion, Resignation and Sainthood; 16: Schopenhauer on the Metaphysics of Art and Morality; 17: Schopenhauer on the Value of Compassion; 18: Schopenhauer and Indian Philosophy19: Life-Denial versus Life-Affirmation: Schopenhauer and Nietzsche on Pessimism and Asceticism; 20: Schopenhauer on the Inevitability of Unhappiness; Part V: Schopenhauer's Context and Legacy; 21: Schopenhauer and Freud; 22: Schopenhauer's Impact on European Literature; 23: Schopenhauer, Nietzsche, Wagner; 24: Schopenhauer's Influence on Wittgenstein; 25: Schopenhauer's Fairy Tale about Fichte: The Origin of The World as Will and Representation in German Idealism; Index.
Print version record.
Keywords: Schopenhauer, Arthur, -- 1788-1860.; Schopenhauer, Arthur, -- 1788-1860